Smart Dumpster Monitoring System - Premkumar, R; K, Jayanarayani; J, Lavanya; A.G, Nirubaa; K, Thirupurasundari (International Journal of Engineering and Technology, 2018)
The project is about smart way of collecting and disposing garbage. A system is designed by automatic opening and closing of the lid when the sensor senses the hand motion. The level of the wastes is measured using sonar sensor and the smell from the waste is detected using gas sensor. In order to avoid the smell, sprayer is placed inside the dustbin which is activated when the signal is sent. There is a motor attached to the lid is used to compress the garbage for further dumping. Once the bin is fully filled the lid is closed automatically and a message is send through GSM. The status of the bin will be displayed as a message outside the bin using LCD display. The problem of overflowing of garbage and the smell will be avoided leading to a good hygienic environment.Â Â